Anterior cervical corpectomy and fusion in a 7-year-old boy: a case report (Medical Journal of Indonesia, 2019)
Bicycle mishap, a common and ordinary event occurring in children, can have devastating consequences associated with cervical spine injury. Furthermore, either diagnosis or surgical management of cervical spine injury in children is a challenging issue. This research report a challenging case of an anterior cervical corpectomy and fusion with plating in a 7-year-old boy due to cervical spine instability with spinal cord compression after a bicycle mishap. After 20 months of the primary surgery, the titanium-based cervical plate was removed by a second surgery to allow the growth of the cervical spine.